BMP6-induced modulation of the tumor micro-milieu - Stieglitz, David; Lamm, Susanne; Braig, Simone; Feuerer, Lena; Kuphal, Silke; Dietrich, Peter; Arndt, Stephanie; Echtenacher, Bernd; Hellerbrand, Claus; Karrer, Sigrid; Boßerhoff, Anja Katrin (Oncogene, 2019)
Melanoma is the deadliest form of skin cancer with rising incidence, creating a significant health problem. We discovered increased expression of bone morphogenetic protein 6 (BMP6) in melanoma cells and tissues, and observed that BMP6 deficiency caused significantly delayed tumor onset and decelerated tumor progression in a melanoma mouse model. Moreover, we determined that BMP6 inhibits dermal mast cell recruitment and found that mast cell-derived mediators significantly reduced melanoma growth in vitro. In line with this, mast cell deficiency accelerated tumor onset and progression in a melanoma mouse model. Analysis of human melanoma tissues revealed a strong negative correlation between melanoma proliferation and mast cell infiltration. This study elucidates a novel role of BMP6-induced modulation of the tumor microenvironment.
EVALuna2:106826